Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1080/02701367.2006.10599337
|View full text |Cite
|
Sign up to set email alerts
|

Athletes' Evaluations of Their Head Coach's Coaching Competency

Abstract: This study provided initial validity evidence for multidimensional measures of coaching competency derived from the Coaching Competency Scale (CCS). Data were collected from intercollegiate men's (n = 8) and women's (n = 13) soccer and women's ice hockey teams (n = 11). The total number of athletes was 585. Within teams, a multidimensional internal model was retained in which motivation, game strategy, technique, and character building comprised the dimensions of coaching competency. Some redundancy among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 30 publications
2
66
0
2
Order By: Relevance
“…As far as coaching competency is concerned, Myers et al (2006) stated that there were three competency domains that were in the National Standards for Athletic Coaches (National Association for Sport and Physical Education, 1995) but were left out of the Coaching Behaviour Questionnaire. These competencies were listed as (a) growth, development and learning of athlete, (b) psychological aspects of coaching, and (c) skills, tactics, and strategies.…”
Section: Research Questionsmentioning
confidence: 99%
See 4 more Smart Citations
“…As far as coaching competency is concerned, Myers et al (2006) stated that there were three competency domains that were in the National Standards for Athletic Coaches (National Association for Sport and Physical Education, 1995) but were left out of the Coaching Behaviour Questionnaire. These competencies were listed as (a) growth, development and learning of athlete, (b) psychological aspects of coaching, and (c) skills, tactics, and strategies.…”
Section: Research Questionsmentioning
confidence: 99%
“…The specific competencies measured by the CCS included: character building competency (CBC), game strategy competency (GSC), motivation competency (MC), and technique competency (TC). The CCS had been validated and tested for reliability in their research on athletes' evaluation of their head coach's coaching competency and found to be psychometrically sound (Myers et al, 2006).…”
Section: Research Questionsmentioning
confidence: 99%
See 3 more Smart Citations